1999
DOI: 10.1002/(sici)1099-0690(199904)1999:4<737::aid-ejoc737>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

100 Years of Baeyer–Villiger Oxidations

Abstract: In the present review, we report the discovery of the formation of esters and lactones by oxidation of ketones with a peroxide derivative, namely the Baeyer–Villiger reaction. This reaction was first reported by Adolf von Baeyer and Victor Villiger a century ago in 1899, just one year after the oxidant they used (KHSO5) has been described. Furthermore, Baeyer and Villiger established the composition of this new inorganic peroxide and showed that its instability was the reason of a controversy between several E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
315
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 554 publications
(338 citation statements)
references
References 99 publications
19
315
0
4
Order By: Relevance
“…Because the Baeyer-Villager (B-V) reaction is known to be mediated (62) by oxidative enzymes (e.g., cytochrome P450), which are present in the nasopharyngeal mucus layer (2,32,63,64), and the B-V reaction of deuterated cyclic ketones forming deuterated lactones is known to show an isotope effect (62), such a reaction might affect odor perception of pairs such as 1 and 1-d 28 . Indeed, we have confirmed that 1-d 28 undergoes peracid-mediated B-V oxidation faster than nondeuterated 1, in accord with literature results (62), although a full kinetic analysis in the case of 1/1-d 28 was not possible due to partial overlap of ketone and lactone peaks under GC-MS conditions.…”
Section: Response Of a Human Musk Or To Deuterated And Nondeuteratedmentioning
confidence: 99%
“…Because the Baeyer-Villager (B-V) reaction is known to be mediated (62) by oxidative enzymes (e.g., cytochrome P450), which are present in the nasopharyngeal mucus layer (2,32,63,64), and the B-V reaction of deuterated cyclic ketones forming deuterated lactones is known to show an isotope effect (62), such a reaction might affect odor perception of pairs such as 1 and 1-d 28 . Indeed, we have confirmed that 1-d 28 undergoes peracid-mediated B-V oxidation faster than nondeuterated 1, in accord with literature results (62), although a full kinetic analysis in the case of 1/1-d 28 was not possible due to partial overlap of ketone and lactone peaks under GC-MS conditions.…”
Section: Response Of a Human Musk Or To Deuterated And Nondeuteratedmentioning
confidence: 99%
“…As a result, acid 2a was obtained with 91 % yield. Based on the Baeyer-Villiger oxidation mechanism [2][3][4][5][6] it is possible to believe that the performic acid reacts with 2-formyloxycyclododecanone 5 to form ether 10 (R = H). Consequently, isolation of 2a with high yield upon oxidation of 5 confirms the ability of ether 10 to be oxidized with formation of acid 2a.…”
Section: R Can Be = H Me Hc=o O=c (H) Omentioning
confidence: 99%
“…The Baeyer-Villiger reaction [1][2][3][4][5][6], known already for more than a century, has found wide application in synthesis of lactones and ω-hydroxycarboxylic acids. The oxidation of acetals (obtained from cyclic ketones) under action of peracids was investigated in a small number of works [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Although several reviews on the BV reactions have been published, which covers the development of the BV oxidation, the concerned oxidants, corresponding catalysts, etc. [27,28], no review aiming at the specific Sn-based catalysts for BV oxidation by using H2O2 as oxidant was published.…”
Section: Introductionmentioning
confidence: 99%